2020
DOI: 10.2217/rme-2020-0062
|View full text |Cite|
|
Sign up to set email alerts
|

Photoencapsulated-BMP2 in vIsible Light-Cured Thiol-Acrylate Hydrogels for Craniofacial Bone Tissue Engineering

Abstract: Aim: The study aimed to examine the impact of crosslinking BMP2 in biodegradable visible light-cured thiol-acrylate hydrogels. Materials & methods: BMP2 was photoencapsulated in 10 wt% PEG-diacrylate hydrogels with or without immortalized mouse bone marrow stromal cells (BMSC). Results & conclusion: Photoencapsulated-BMSC with BMP2 (BMBMP2) showed a significantly (p < 0.05) increased level in metabolic activity, by 54.61%, compared with photoencapsulated-BMSC at day 3. Furthermore, BMBMP2 groups sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…BMSCs are adult multipotent stem cells derived from bone marrow tissue [ 47 ]. BMSCs are a promising cell source due to their self-renewal and multipotency by differentiating into different cell types, such as osteoblasts, chondrocytes, and adipocytes [ 125 , 206 , 209 , 223 , 224 , 225 , 226 , 227 , 228 , 229 ].…”
Section: Mesenchymal Stromal Cells: Successes and Challengesmentioning
confidence: 99%
See 4 more Smart Citations
“…BMSCs are adult multipotent stem cells derived from bone marrow tissue [ 47 ]. BMSCs are a promising cell source due to their self-renewal and multipotency by differentiating into different cell types, such as osteoblasts, chondrocytes, and adipocytes [ 125 , 206 , 209 , 223 , 224 , 225 , 226 , 227 , 228 , 229 ].…”
Section: Mesenchymal Stromal Cells: Successes and Challengesmentioning
confidence: 99%
“…Accordingly, there has been an increasing interest in using BMSCs for cranial bone regeneration. Recently, we have shown that photoencapsulated BMSCs in fast degrading thiol acrylate hydrogels promote new bone formation in rabbit calvarial defects, compared to negative control group, 6 weeks post-implantation [ 24 , 47 ], Figure 3 . Other studies have shown similar conclusions using BMSCs to regenerate critical-size bone defects [ 50 , 236 , 237 ].…”
Section: Mesenchymal Stromal Cells: Successes and Challengesmentioning
confidence: 99%
See 3 more Smart Citations